859. Same-Day HIV Pre-exposure Prophylaxis (PrEP) Initiation During Drop-in STD Clinic Appointments Is a Safe, Feasible, and Effective Method to Engage Patients at Risk for HIV in PrEP Care. (26th November 2018) - Kamis, Kevin; Scott, Kenneth; Gardner, Edward; Wendel, Karen; Marx, Grace; Scott, Mia; Montgomery, Angela; Rowan, Sarah
Abstract: Background: Patients at risk for HIV generally do not have immediate access to PrEP. We hypothesized that by offering free, 30-day PrEP starter packs and navigation support during drop-in STD clinic appointments, individuals would be likely to initiate and continue PrEP. Methods: Individuals aged ≥18 years presenting for drop-in appointments in the Metro Denver STD Clinic and indicated for PrEP were eligible for the study. Exclusion criteria were history of renal dysfunction, chronic hepatitis B (HBV), HIV, pregnancy, and indications for postexposure prophylaxis. Eligible individuals were provided PrEP education and offered a free, 30-day PrEP starter pack and navigation support for cost assistance. Participants were tested for creatinine, HBV, HIV, and pregnancy at enrollment, and navigated to an appointment for ongoing PrEP care. Participants' medical records were reviewed for a minimum of 4 months after enrollment. Descriptive statistics and logistic regression were used to characterize the study population and follow-up. Results: From April to October 2017, 100 individuals filled a tenofovir–emtricitabine prescription (figure). Median participant age was 28 years, 98% were male, 53% were non-Hispanic White, 8% non-Hispanic Black, and 34% Hispanic. Median annual income was $24, 000, 62% had health insurance, 26% had a primary care provider (PCP), and 50% had a recent bacterial STI. No participants had abnormal baseline creatinine or HBV. 77% completed ≥1 PrEP follow-up visit during the study period; 57% completed their first visit within 31 days. 56% completed a second follow-up visit. No HIV seroconversions were detected during follow-up. Factors significantly associated with attending ≥1 follow-up appointment were age ≥ 30 years, higher income, and having health insurance or a PCP at enrollment. In multivariate logistic regression, only higher income was associated with attending ≥1 follow-up appointment (median income for those with ≥1 follow-up visit vs. no follow-up: $24, 960 vs. $14, 000, P <0.01). Conclusion: Providing immediate access to PrEP during drop-in STD clinic visits is a safe and feasible approach to initiation of PrEP care. Additional resources are needed to support PrEP continuity care, particularly for low-income individuals. Disclosures: K. Kamis, Gilead Scienes: Research Coordinator, Research grant. S. Rowan, Gilead Sciences: Investigator, Research grant.